2017
DOI: 10.3758/s13414-017-1382-x
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-haptic integration in object identification using novel objects

Abstract: Although some studies have shown that haptic and visual identification seem to rely on similar processes, few studies have directly compared the two. We investigated haptic and visual object identification by asking participants to learn to recognize (Experiments 1, and 3), or to match (Experiment 2) novel objects that varied only in shape. Participants explored objects haptically, visually, or bimodally, and were then asked to identify objects haptically and/or visually. We demonstrated that patterns of ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…However, this may be, our results support Kennedy (1993) that people deprived of vision can accurately process 2D spatial information about objects at a similar level as sighted individuals, in our case by making use of a combination of information based on contours and textures. In a series of experiments, Desmarais et al (2017) consistently demonstrated that haptic and visual object identification are based on similar processes which may possibly share memory representations that contain shape information.…”
Section: Discussionmentioning
confidence: 96%
“…However, this may be, our results support Kennedy (1993) that people deprived of vision can accurately process 2D spatial information about objects at a similar level as sighted individuals, in our case by making use of a combination of information based on contours and textures. In a series of experiments, Desmarais et al (2017) consistently demonstrated that haptic and visual object identification are based on similar processes which may possibly share memory representations that contain shape information.…”
Section: Discussionmentioning
confidence: 96%
“…While we think of softness as primarily a mechanical property that can be perceived through touch (Klatzky & Lederman, 1987;Cellini et al, 2013;Okamoto et al, 2013;Di Luca, 2014;Higashi et al, 2019;Kitada et al, 2019;Cavdan et al, 2019;Dovencioglu et al, 2020;Xu et al, 2020) softness can also be judged visually (Drewing et al, 2009;Giesel & Zaidi, 2013;Baumgartner et al, 2013;Bouman et al, 2013;Bi et al, 2018;Schmid & Doerschner, 2018). This latter ability is most likely acquired through countless multisensory interactions with objects in the environment, where simultaneous activation of visual and haptic senses leads to strong associations across modalities (Lacey et al, 2010;Yildirim & Jacobs, 2013;Desmarais et al, 2017). For example, while exploring a type of fabric (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 22, 2021. ; https://doi.org/10.1101/2021.01.22.427730 doi: bioRxiv preprint environment, where simultaneous activation of visual and haptic senses leads to strong associations across modalities (Lacey et al, 2010;Yildirim & Jacobs, 2013;Desmarais et al, 2017). For example, while exploring a type of fabric (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers study different exploratory procedures that humans apply for tactile object recognition [2] and reveal the superiority of tactile perception in presence of vision [4]. Demarais et al [6] studied the performance of visual, tactile, and bimodal exploration of objects for both learning and testing procedures for object identification.…”
Section: State-of-the-artmentioning
confidence: 99%